Influence of periodic leg movements in sleep on stroke outcome. Issue 3 (25th June 2013) - Benbir, Gulcin; Karadeniz, Derya
Abstract: Destructive lesions, as cerebrovascular diseases, have been shown to lead to the development of periodic leg movements in sleep (PLMS), secondary to the loss of cortical or subcortical inhibition exerting on the brainstem generators. We designed a prospective study to investigate the association of PLMS with a clinical outcome in 24 patients with acute ischemic cerebrovascular diseases. The medical history of patients and risk factors of ischemic stroke were questioned. A whole‐night polysomnographic (PSG) recording was performed; detailed PSG data including PLM index and PLM‐arousal index were analyzed. Stroke outcome was assessed at 3 weeks and 3 months by the National Institute of Health Stroke Scale (NIHSS) and Barthel Scale (BS). The results of NIHSS and BS were correlated with demographic parameters and PSG parameters including PLMS data. However, none of them showed a significant correlation with clinical parameters. The delta change in outcome measures was correlated with the PLMS index, which was also not significantly different at the subacute or chronic phase. On the other hand, the correlation between delta changes in mean NIHSS and BS with mean arousal‐associated PLMS index showed a borderline significance at the subacute stage, and significant correlation was observed at the chronic phase. Increased sympathetic activation secondary to RLS or arousal reactions following PLMS have been suggested as the underlying pathophysiology of cardiovascular complications. PLMS, particularly with accompanying autonomic arousal, may therefore be a risk factor for stroke, and display a negative influence on stroke outcome.